Eye movement desensitization and reprocessing for depression: a systematic review and meta-analysis. Issue 1 (1st January 2021) - Carletto, Sara; Malandrone, Francesca; Berchialla, Paola; Oliva, Francesco; Colombi, Nicoletta; Hase, Michael; Hofmann, Arne; Ostacoli, Luca
ABSTRACT: Background : In recent years, eye movement desensitization and reprocessing (EMDR) has been applied to different psychiatric conditions beyond post-traumatic stress disorder (PTSD), and an increasing number of studies have evaluated its effect on depression. To date, no quantitative synthesis of the efficacy of EMDR on depression has been conducted. Objective : To meta-analytically review the studies on EMDR for depression as the primary target for treatment. Method : Studies with a controlled design evaluating the effect of EMDR on depression were searched on six electronic databases (PubMed, Embase, CINAHL, PsycINFO, Cochrane database, and Francine Shapiro Library) and then selected by two independent reviewers. A systematic review and meta-analysis was conducted. Results : Eleven studies were included for qualitative synthesis. Nine studies were included in the meta-analysis, involving 373 participants. The overall effect size of EMDR for depressive symptoms is large ( n = 9, Hedges' g = – 1.07; 95%CI [–1.66; – 0.48]), with high heterogeneity ( I 2 = 84%), and corresponds to a 'number needed to treat' of 1.8. At follow-up (range 3–6 months), the effect remains significant but moderate ( n = 3, Hedges' g = – 0.62; 95%CI [–0.97; – 0.28]; I 2 = 0%). The effect of EMDR compared with active controls is also moderate ( n = 7, g = – 0.68; 95%CI [–0.92; – 0.43]; I 2 = 0%). No publication bias was found, although the results are limited by the small number and poor methodological quality of the included studies. Conclusions : Review findings suggest that EMDR may be considered an effective treatment for improving symptoms of depression, with effects comparable to other active treatments. However, findings need to be interpreted in light of the limited number of the studies and their quality. Further research is required to understand the longer-term of effects EMDR in treating depression and preventing depression relapse. Protocol registration : PROSPERO (CRD42018090086). HIGHLIGHTS: This review summarizes the current evidence on the effects of EMDR for depression. Findings show that one-third of people with depression could benefit from EMDR. EMDR could be considered as an alternative to first-line treatments for depression, pending further research.